Telescopes and Techniques - Kitchin, C. R.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Telescopes and Techniques has proved itself in its first two editions, having become probably one of the most widely used astronomy texts, both for amateur astronomers and astronomy and astrophysics undergraduates. Both earlier editions of the book were widely used for introductory practical astronomy courses in many universities. In this Third Edition the author guides the reader through the mathematics, physics and practical techniques needed to use today's telescopes (from the smaller models to the larger instruments installed in many colleges) and how to find objects in the sky. Most of the physics and engineering involved is described fully and requires little prior knowledge or experience. Both visual and electronic imaging techniques are covered, together with an introduction to how data (measurements) should be processed and analyzed. A simple introduction to radio telescopes is also included. Brief coverage of the more advanced topics of photometry and spectroscopy are included, but mainly to enable the reader to see some of the developments possible from the basic observing techniques covered in the rest of the book. For anyone intending to enter astronomy as a professional, an understanding of the physics is essential - and this newest version of Telescopes and Techniques is one of the best starting points!
Preface to the First Edition -- Preface to the Second Edition -- Preface to the Third Edition -- Part I: Telescopes -- Chapter 1: Types of Telescopes -- Chapter 2: Telescope Optics -- Chapter 3: Modern Small Telescope Design -- Part II: Positions and Motions -- Chapter 4: Positions in the Sky -- Chapter 5: Movements of Objects in the Sky -- Chapter 6: Telescope Mountings -- Part III: Observing -- Chapter 7: Electromagnetic Radiation -- Chapter 8: Visual Observing -- Chapter 9: Detectors and Imaging -- Chapter 10: Data Processing -- Chapter 11: Photometry -- Chapter 12: Spectroscopy -- Appendix A: For Further Reading -- Appendix B: Constellations -- Appendix C: Answers to Exercises -- Appendix D: SI and Other Units -- Appendix E: The Greek Alphabet -- Index.
Keywords: Physics; Physics; Astronomy, Observations and Techniques; Optics, Optoelectronics, Plasmonics and Optical Devices; Spectroscopy and Microscopy